2003
DOI: 10.1002/chin.200307217
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Vanadium‐Based Catalysts for the Ziegler—Natta Polymerization of α‐Olefins

Abstract: Although their activity is often inferior to that of other systems, the use of vanadium-based catalysts in homogeneous Ziegler-Natta polymerizations allows the preparation of high-molecular-weight polymers with narrow molecularweight distributions, ethene/a-olefin copolymers with high a-olefin incorporation, and syndiotactic polypropene. The main reason for the low activity of these catalysts is their deactivation during catalysis by reduction of active vanadium species to low-valent, less active or inactive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
8
0
2
Order By: Relevance
“…化 合 物 , 例 如 VCl 4 , VOCl 3 , VO(OR) 3 , VOCl(OR) 2 , VOCl 2 (OR)和V(acac) 3 等, 其中R为烷基, acac为乙酰 丙酮 [8] . 中心金属钒具有多个价态, 但并不是所有价 态的钒都具有催化活性, 因此, 选择主催化剂时还要 考虑中心金属钒的价态.…”
Section: 钒系催化剂的主催化剂通常为可溶于烷烃的钒unclassified
“…化 合 物 , 例 如 VCl 4 , VOCl 3 , VO(OR) 3 , VOCl(OR) 2 , VOCl 2 (OR)和V(acac) 3 等, 其中R为烷基, acac为乙酰 丙酮 [8] . 中心金属钒具有多个价态, 但并不是所有价 态的钒都具有催化活性, 因此, 选择主催化剂时还要 考虑中心金属钒的价态.…”
Section: 钒系催化剂的主催化剂通常为可溶于烷烃的钒unclassified
“…et al reported that either VOCl3/Et3Al2Cl3 or VO(OtBu)3/Et3Al2Cl3 showed high cyclic dienes incorporation ability in the terpolymerization with ethylene and propylene [23]. Since the vanadium catalysts might be deactivated during the polymerization because of the reduction to low-valent, inactive species [27], introduction of bulky and polydentate ancillary ligands to stabilize active vanadium(V) species has been proven to be an effective approach to keep vanadium at high-oxidation and subsequently prolong the catalytic lifetime [28][29][30][31][32][33][34][35][36]. In our previous work, the synthesized [ONNO]-type and [ONN]-type oxovanadium(V) complexes also showed high catalytic activities and promising stabilities in copolymerization of ethylene with norbornene (NBE), and produced E/NBE copolymers with high NBE contents [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…and Et 2 AlCl, EtAlCl 2 , n BuLi, etc.] display unique high reactivity toward olefins in olefin coordination/insertion polymerization [1][2][3][4][5]. We previously reported that (arylimido)vanadium(V) complexes, containing anionic donor ligands (L), V(N-2,6-Me 2 C 6 H 3 )Cl 2 (L) (L = aryloxo, ketimide, phenoxyimine etc.…”
Section: Introductionmentioning
confidence: 99%
“…We thus speculated that a reason for the observed difference would be due to a formation of the different catalytically-active species, catalyst/cocatalyst nuclearity effect (assumed in Scheme 1) [5,[11][12][13]. The activity decreased upon addition of CCl 3 CO 2 Et (for example, [14]), which can be commonly used as effective additives to improve the catalyst stability [8], clearly suggesting that the active species were, thus, different from those prepared from vanadium(III), (IV) complexes [1][2][3][4][5]14]. More recently, we demonstrated that the (adamantylimido)vanadium(V) complexes containing (2-anilidomethyl)pyridine ligand, V(NAd)Cl 2 [2-ArNCH 2 (C 5 H 4 N)] [Ad = 1-adamantyl; Ar = 2,6-Me 2 C 6 H 3 (1a), 2,6-i Pr 2 C 6 H 3 (1b)], efficiently dimerize ethylene with both notable catalytic activities, and high selectivity in the presence of MAO [15,16], whereas the reaction products by 1a,b in the presence of Me 2 AlCl or Et 2 AlCl cocatalyst were ultrahigh molecular weight polyethylene (PE) (runs 1-5, Table 1) [16].…”
Section: Introductionmentioning
confidence: 99%